Autonomic cardiac regulation and morpho-physiological responses to eight week training preparation in junior soccer players - Botek, M.; Krejci, J.; Weisser, R. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2014)
Training preparation in soccer is thought to improve body composition and performance level, especially the maximal aerobic capacity (VO2max). However, an enhancement in performance may be attenuated by the increase of fatigue. Heart rate variability (HRV) as a non-invasive index of autonomic nervous system (ANS) activity has been considered to be a sensitive tool in fatigue assessment. Objective: This study was focused to evaluate the response of ANS activity and morpho-physiological parameters to eight week training preparation. Methods: Study included 12 trained soccer players aged 17.2 ± 1.2 years. Athletes underwent pre- and post-preparation testing that included the ANS activity assessment by spectral analysis of HRV in supine and upright position. Further, body composition was analyzed via electrical bio-impedance method and physiological parameters were assessed during maximal stress tests. ANS activity and subjective feeling of fatigue was assessed continuously within subsequent weeks of preparation. Results: No significant differences in all HRV variables within weeks were found. Pre vs. post analyses revealed a significant (p < .05) increase in body weight, fat free mass, body mass index, and peak power. A significant decline in mean maximal heart rate (HR) and resting HR at standing was identified at the end of preparation. Since no significant changes between pre- post-preparation in the mean VO2max occurred, the positive correlation between the individual change in VO2max and the vagally related HRV [supine LnHF (r =?.78), Ln rMSSD (r = .63), and the standing LnHF (r = .73, p < .05)] was found. Conclusions: This study showed that an 8 week training program modified particularly fat free mass and short-term endurance, whereas both the autonomic cardiac regulation and the feeling of fatigue remained almost unaffected. Standing position seems to be more sensitive in terms of the HR response in relation to fatigue perception than supine.